The state of the art of strategic planning in selected South African companies - J. H. McIntosh; A. A. Archer (South African Journal of Business Management, 1986)
Numerous overseas studies have concluded that formal planning of company operations was uncommon and strategic planning even rarer. Those companies professing formal planning systems were found to use little more than extended budgeting. However, some of these studies did find a trend towards more systematic planning practices. The aim of this study was to determine whether a similar trend exists among selected South African companies. The survey results indicate that although all respondents have progressed beyond the informal planning stage, some still only practise basic financial planning and extended budgeting. The majority of respondents practise forecast-based planning and only a few have reached the externally orientated planning stage. Findings indicate that none of the respondents practise strategic management. These conclusions, as well as respondents' reasons for planning failure, have implications for chief executives and planners, and indicate areas of future research.
Keywords: 650